Case report of mucha-habermann disease - Lokhande, Archana J; Soni, Rohini; Mahto, Santosh Kumar; Dhali, Tapan Kumar (Indian Journal of Case Reports, 2018)
Pityriasis lichenoides et varioliformis acuta (PLEVA), also known as a Mucha-Habermann disease, is an uncommon, idiopathic, and acquired dermatosis. The disease is characterized by erythematous, scaly, papules, and polymorphic lesions which often progresses to hemorrhagic necrosis and heals with varioliform scarring. A febrile ulceronecrotic variant of PLEVA, also termed pityriasis lichenoides (PL) with ulceronecrosis and hyperthermia (PLUH) or febrile ulceronecrotic Mucha-Habermann disease (FUMHD), is a severe variant of PLEVA. The disease is characterized by the acute onset of large, more destructive, coalescent papules, leading to ulceronecrotic skin lesions associated with high fever and other systemic symptoms. In spite of the presence of multiple treatment modalities with variable success rate, the disease has poor prognosis. Here, we report the case of a 17-year-old male patient who presented with typical features of FUMHD and responded well to systemic administration of corticosteroid therapy.